Pengaruh Beban Kerja Dan Stres Kerja Terhadap Kinerja Karyawan Pada CV Nusantara Cipta Pratama: The Effect of Workload and Work Stress on Employee Performance at CV Nusantara Cipta Pratama - Muhammad Alifiandra Arrauf Firman; Mohammad Amas Lahat; Dani Chandra Utama (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study aims to analyze the Effect of Workload (X1) and Work Stress (X2) on Employee Performance (Y) at CV Nusantara Cipta Pratama, Tangerang City. Data were collected using a questionnaire involving 30 employees at the head office of CV Nusantara Cipta Pratama. The results of the analysis using IBM SPSS V.26 software showed that Workload (X1) had a positive and significant effect on Employee Performance (Y) with a t-count of 10.428> t-table 2.052 and a significance level of 0.000 <0.05. On the other hand, Work Stress (X2) did not have a positive and significant effect on Employee Performance (Y) where the t-count value was -1.295> 2.052 and a significance level of 0.206> 0.05. Simultaneously, the results of the F Test show that Workload (X1) and Job Stress (X2) have a positive and significant effect on Employee Performance (Y) where the f-value is 55.862> f-table 3.354 and the significance level is 0.000 <0.05. This study concludes that Workload and Job Stress have a positive and significant effect simultaneously on Employee Performance at CV Nusantara Cipta Pratama, Tangerang City.